Language Changes in Late-Onset Alzheimer’s Disease - Eda Can; Gülmira Kuruoğlu (Психолінгвістика)
Alzheimer’ s disease (AD) is the most common cause of cognitive decline and dementia in the elderly. Language disturbances appear early in AD and constitute an important element of the diagnosis, although they are usually overshadowed by impairment of memory and executive functions. It is known that language is impaired disproportionally in AD: the semantic and pragmatic language systems are more impaired than syntax. However, syntactic features can also be impaired in the moderate and severe stages of AD. The features of language can be different depending on the onset of AD. AD is classified into two subtypes: early-onset (before 65 years of age) and late-onset (over 65 years of age). Late-onset is the most common form of AD and the aim of this study is to reveal the language changes of 39 patients with late-onset AD and compare it with an age/education-matched control group that has no neurological and psychological problems. The data was transcribed using transcript symbols following Du Bois. The results revealed that although the number of the sentences were more, the speech amount of late-onset AD patients was smaller than the control group. Late-onset AD patients mostly produced sentences in “Picnic” picture description test and fewer sentences in random speech test. Moreover, the sentence length of LAD patients was bigger in “Cookie theft” picture description test and smaller in “Picnic” picture description test. However, their general performance about the speech amount was poor. The other findings were about the coordinated and compound sentences. It was revealed that late-onset AD patients used similar number of coordinated and compound sentences compared to their aged matched peers. In conclusion, it is clear that the syntactic features of LAD patients is not completely different from the people with normail aging.